In the Search of Audience : Ideas and Practises of Audience Development in the Regional Dance Centers in Finland - Suonsyrjä, Sanna (Sibelius-Akatemia, 2007)
In this thesis I will examine audience development both in theory and practise from the viewpoint of an arts manager. In my research I concentrate on a very specific section, i.e. audience development in Finnish contemporary dance. To examine this I have interviewed arts managers, i.e. producers or coordinators of the five centers forming the Network of Regional Centers for Dance. These five semi-structured theme interviews form the empirical research material of my study. In the first part of my study I will present different views and approaches to audience development in the light of previous research. I will also discuss areas closely related to audience development such as attendance and marketing. There is no universally accepted definition of audience development but it is generally agreed on that it includes three aspects: artistic, educational and marketing. All through this thesis my approach in understanding audience development includes all three aspects, as well as the thought of audience development including the two major duties of nurturing, both existing and new audiences. The purpose of my study is to find out how audience development is understood in the field of Finnish contemporary dance by arts managers, what the images and practises of it are and what areas are included in it. I also wanted to learn more about the attitudes that prevail towards audience development; whether audience development would be seen as an important area and worth the effort or would it rather be considered as a duty. In addition I wanted to know if practising audience development has effected on the audience either in quality or quantity, or are there some other benefits that might have occurred because of audience development practise. The most important finding of my study is that there are lot of separate activities and projects in the regional dance centers that obviously belong to audience development but detailed plans, strategies and evaluation of the implemented projects are missing. There is a lack of clear strategy with a strategic focus. I believe that by strategy making, focusing and integrating audience development into the organization the regional dance centers would get the most out of their investments and the benefits of audience development would be more visible. This way also their faith in audience development would increase and its position in the organization would strengthen. In order to do that they need to employ the audience champion and have enough funding for the long-term planning. However, the concept of audience development is young in Finland and it has not been funded like e.g. in the UK. Also the network of regional centers for dance is young and it has demanded a lot of resources to find models for operating. Considering this the efforts for audience development in the centers are prominent.
Keywords: tanssi; yleisö; markkinointi; taide; fi=taidehallinto|sv=Arts Management|en=Arts Management|